Estudo das diferenças individuais da psicopatia, por meio daescala hare (pcl-r), no sistema carcerário mineiro - Marco Antonio Silva Alvarenga (2006)
This research intends to verify the profile of prisoners from three different penitentiaries of cities placed in the neighborhood of Belo Horizonte. Its main goal consisted in measuring the level of personality commitment (Psychopathy) of a sample of inmates, through the Psychopathy Checklist-Revised (PCL-R), and, then, associate it with an amount of variables, as the socioeconomic degree (Critério Brasil), the intelligence (Raven Matrizes Progressivas Escala Geral), the diagnosis criteria from DSM-IV to TPAS, and other personality traits composed of four IFP factors Aggressiveness, Dominance, Deference, and Perseverance. Two trained psychologists evaluated 124 inmates whose ages varied from 18 to 77 years (M=30,19; dp=10,22). The scale used to identify the Psychopathy, outputted a rate of internal consistence of 0,836, and a level of agreement between the psychologists previously mentioned greater than 0,94 (p=0,0001) to the F1, F2 and total scores. Considering this, it was possible to generate the factorial components of the PCL-R scale, confirming the presence of two factors in the Hare scale. The study also revealed that the two prisoners who obtained the highest scores in the intelligence test, had the lowest personality commitment. The personality factors, however, werent straightly correlated to the factorials and total scores of the PCL-R. This study brought important academic and professional contributions. The academic contribution consisted in presenting the level of association among different variables, in the internals evaluation. The professional contribution consisted in demonstrating the level of internal consistence of the instrument, allowing it to be used, in the future, in forensic procedures to estimate the probability of recidivism or social reintegration.